IDENTIFYING CATEGORY SHIFTS IN THE ENGLISH-INDONESIAN TRANSLATION OF JOKER (2019) MOVIE - Suardana, I Wayan; Jayantini, I Gusti Agung Sri Rwa; Suastini, Ni Wayan (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
The research focuses on the analysis of category shift in the movie of Joker (2019). This study has two aims, namely (1) to identify the types of category shifts that appear in the English-Indonesian translation of Joker (2019) movie and (2) to describe the use of category shifts of Joker (2019) movie texts on transferring messages from the source language into the target language. Descriptive qualitative method was used in study to analyze the data. In this study, Catford's (1965) theory of translation shifts was applied. The data source of this study was the Joker (2019) movie by Todd Phillips in English with Indonesian subtitles. Observation and documentation method were applied in collecting the data. The subtitle of the film was the object of the observation. The results showed that all types of category shifts presented by Catford were found in the translation. The structure shift occurred in the highest occurrence, consisting of 46 data (43,40%) out of the 106 data. It appeared because there were different classes and functions of the word between English into Indonesian. The fewest occurrence was class shift consisting of 17 data (16,03%). The majority of the class shifts discovered in this study is shifts from noun to a verb. Unit shift occurred 24 cases (22,65%). Most of the unit shifts found in the source language were transferred from words to phrases in the target language and intra-system shift occurred 19 data (17,92%) from the total of 106 data found. This shift was represented by the plural forms in English that were mostly translated into singular forms in Indonesian because, as it can be seen in the translation, the markers of plural quantifier were followed by the singular noun in Indonesian. The plural forms were shown by the use of them in the noun phrases.